Cardiovascular disease in North African women: insights from the Middle East African Women CardioVascular Disease (MEA-WCVD) registry - Charfeddine, Salma; Abid, Leila; Chenik, Sarra; Ben Krayen, Iheb; Haddar, Oussama; Ghrab, Aymen; Boudiche, Selim; Touati, Haithem; Ayedi, Oumaima; Ammar, Mohamed Amine; Ben Halima, Manel; Ben Ayed, Houssem; et al. (Frontiers in Cardiovascular Medicine, 2025)
Cardiovascular disease (CVD) is a major health burden worldwide, yet gender-specific data from the Middle East and North Africa (MENA) region remain scarce. The Middle East African Registry of Women with Cardiovascular Disease enrolled adult patients with coronary heart disease (CHD), heart failure (HF), atrial fibrillation (AF), or valvular heart disease (VHD) across Tunisia between May and July 2023. Of 15,366 patients, 37.6% were women. Compared with men, women were older, had lower socioeconomic status, and presented with more obesity, hypertension, diabetes, dyslipidemia, and sedentary lifestyle but smoked less. CHD was less frequent in women, while AF and VHD were more prevalent. Women underwent fewer coronary angiographies and percutaneous interventions, experienced longer delays, and received fewer guideline-based therapies, including dual antiplatelet agents and high-intensity statins. Among HF patients, women more often had preserved ejection fraction and higher hospitalization rates. These results highlight persistent gender inequities in CVD care in Tunisia.